Evaluating the Effectiveness of Psychosocial Interventions for Empty Nest Syndrome: A Systematic Review - Liji Sara Varghese; Dr. S. Vasantha (The Bioscan, 2024)
Background: Empty nest syndrome is a psychological condition that affects parents when their children leave home and it leads to feelings of loneliness and depression. Although several psychological therapies have been created to lessen these consequences, their effect remains unknown. Objective: The objective of this systematic review is to assess and compare the efficacy of various psychosocial therapies in reducing empty nest symptoms in the elderly. Methods: A comprehensive literature search was conducted for research articles, using the terms “empty nest syndrome," “empty nesters”, “elderly”, “older adults”, "psychosocial interventions," “therapies”, "cognitive-behavioral therapy," “group therapy” and "social support”. Database includes PubMed, Psyc INFO, Web of Science, and CINAHL databases. Results: Seven empirical studies were discovered to be relevant to our research. The effect of Cognitive Behaviour Therapy (CBT), Group Psychological Intervention, Path-Oriented Psychological Self-Help Interventions, Self-Mutual- Group Model (SMG Model), and Group Based Acceptance Commitment Therapy (ACT) on empty nest syndrome is evaluated. It has been discovered that these interventions have a positive impact on the mental health, quality of life, social interactions, and well-being of elderly empty nesters. Conclusion: As this review indicates, empowering empty nest syndrome in older people with psychosocial therapies may significantly alleviate symptoms and enhance their overall well-being. Empty nesters' quality of life and mental health can be improved by implementing various empowering methods, which will help minimize the negative impacts of empty nest syndrome.